Editorial overview to the Special Issue ‘Wildfires in a changing world’ - Volkova, Liubov; Fernandez, María Elena (Elsevier, 2024)
Fire is an important component of many forest ecosystems, yet climate change is now modifying fire regimes all over the world, driving a need to understand the impact of fires on the physical and biological processes. In 2022, Elsevier launched a Special Collection that spanned across several journals, inviting papers under the theme of fires. Here we summarize the articles published in this collection, considering them to be broadly grouped into following themes: impact of fires on flora and fauna, fire modelling, and reshaping forest landscapes.